2017
DOI: 10.1101/182444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The modulation of neural gain facilitates a transition between functional segregation and integration in the brain

Abstract: Cognitive function relies on a dynamic, context-sensitive balance between functional integration and segregation in the brain. Previous work has proposed that this balance is mediated by global fluctuations in neural gain by projections from ascending neuromodulatory nuclei. To test this hypothesis in silico, we studied the effects of neural gain on network dynamics in a model of large-scale neuronal dynamics. We found that increases in neural gain pushed the network through an abrupt dynamical transition, lea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 61 publications
3
75
0
Order By: Relevance
“…We used the model to test the hypothesis that differences in gain modulation and/or changes in global coupling could explain the double dissociation observed in the data. Gain increase under catecholamines has been established for the input-output functions of single cortical neurons 1,6,30 as well as of neural mass activity assessed with neuroimaging 14,19 . Our simulations showed that an increase in gain was, in fact, sufficient to explain the context-dependent effect of atomoxetine on cortical correlations (Fig.…”
Section: Fig 2 Circuit Mechanisms Of Context-dependent Effects On Cmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the model to test the hypothesis that differences in gain modulation and/or changes in global coupling could explain the double dissociation observed in the data. Gain increase under catecholamines has been established for the input-output functions of single cortical neurons 1,6,30 as well as of neural mass activity assessed with neuroimaging 14,19 . Our simulations showed that an increase in gain was, in fact, sufficient to explain the context-dependent effect of atomoxetine on cortical correlations (Fig.…”
Section: Fig 2 Circuit Mechanisms Of Context-dependent Effects On Cmentioning
confidence: 99%
“…We set out to test for differences between the signatures of catecholaminergic and cholinergic neuromodulation in large-scale cortical network dynamics in the human brain. Our approach was based on the recent insight from computational neuroscience that the brain-wide interaction of subtle local microcircuit effects can give rise to substantial effects at the level of large-scale cortical networks 13,14 . We (i) used selective pharmacological interventions to increase central catecholamine and acetylcholine levels in healthy human participants, (ii) measured the effects of these interventions on large-scale cortical network dynamics (assessed with magnetoencephalography; MEG) and behavior, and (iii) simulated cortical circuit models in order to develop a mechanistic understanding of our empirical results.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models and empirical findings have linked higher gain to increases in the topological complexity and variability of population activity (Shine et al, 2018;Moyal & Edelman, 2019) as well as to enhanced inter-regional information transfer (Li et al, 2019). Asterisks denote a significant difference (p < .05*, p < .01**, p < .001***).…”
Section: Temporal Selection Boosts Visual Processing 23mentioning
confidence: 99%
“…It is also unclear to what extent temporal selection affects coordination among different brain regions. LC activation may lead to the dynamic reconfiguration of cortical functional networks (Shine et al, 2018;Li et al, 2019), which is thought to play role in the formation and maintenance of complex sensory representations (Fries, 2005(Fries, , 2015. Enhanced functional connectivity (Friston, 2011) between the hippocampus and visual areas, in particular, has been linked to better working memory (Gazzaley et al, 2004) and episodic encoding (Ranganath et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Neural gain captures how quickly the efferent firing rate of a neural population responds to changes in afferent input. Only recently has the gain function in dynamic brain network models been subject to parametric manipulation [18]. The paper of Kringelbach et al represents a first in the use of independent data to inform the regional heterogeneity of this important effect (Figure 2).…”
Section: Current Biologymentioning
confidence: 99%